Domestication and microbiome succession may drive pathogen spillover - Apari, Péter; Földvári, Gábor (Frontiers in Microbiology, 2023)
Emerging infectious diseases have posed growing medical, social and economic threats to humanity. The biological background of pathogen spillover or host switch, however, still has to be clarified. Disease ecology finds pathogen spillovers frequently but struggles to explain at the molecular level. Contrarily, molecular biological traits of host-pathogen relationships with specific molecular binding mechanisms predict few spillovers. Here we aim to provide a synthetic explanation by arguing that domestication, horizontal gene transfer even between superkingdoms as well as gradual exchange of microbiome (microbiome succession) are essential in the whole scenario. We present a new perspective at the molecular level which can explain the observations of frequent pathogen spillover events at the ecological level. This proposed rationale is described in detail, along with supporting evidence from the peer-reviewed literature and suggestions for testing hypothesis validity. We also highlight the importance of systematic monitoring of virulence genes across taxonomical categories and in the whole biosphere as it helps prevent future epidemics and pandemics. We conclude that that the processes of domestication, horizontal gene transfer and microbial succession might be important mechanisms behind the many spillover events driven and accelerated by climate change, biodiversity loss and globalization.